Significance of organizational health features during the COVID-19 pandemic for the well-being of Lithuanian healthcare workers - Kukulskienė, Milda; Argustaitė-Zailskienė, Gita; Griciūtė, Aušra; Miglinė, Vilma; Kubilienė, Loreta; Žemaitienė, Nida (Frontiers in Psychology, 2023)
Summary During various emergencies, especially pandemics, there is a heavy burden on healthcare workers and pharmacists. Organizational support plays a significant role in protecting their mental health. Though the study aimed analyze the subjectively perceived difficulties and challenges of healthcare workers related to organizing work in the context of a pandemic. Methods Twenty seven subjects (20 women, 7 men) participated in the qualitative research 30–45 min. Duration semi-structured interviews were performed, and thematic data analysis was applied. Results During the first wave of the COVD-19 pandemic, research participants experienced an avalanche of change in all significant areas of life: experienced general overall uncertainty, confusion in working order, and intense changes in work functions, responsibilities, and workload. These changes reduced the scope for control and predictability, there was a lack of structure and clarity. The avalanche of change caused by the COVID-19 pandemic provoked a strong and controversial emotional response. The contradiction was revealed between helplessness, disruption, loss of control experienced by staff and the internal and external pressure to adapt as quickly as possible to the functions of caregivers. The threats posed by the pandemic reinforced the need for active and engaged leadership and highlighted the key features of an employee supporting organization. Conclusion Surviving the avalanche of change caused by the pandemic, healthcare workers and pharmacists emphasized the importance of management decisions about managing patient and employee health threats, clear work organization, active and inclusive leadership, change planning, and organizational concern for employee sustainability and emotional well-being. Regular, systematic, clear and understandable, timely, open and sincere, uncontroversial, and consistent communication of administration provides security for employees and can contribute to better physical and psychological well-being of employees.